Aktivitas Antibakteri Ekstrak Etanol dan Dekokta Daun Jambu Kristal (Psidium guajava L. Cultivar Kristal) Terhadap Bakteri Escherichia coli dan Shigella sonnei - Wardhani, Agviolisa Kusuma; Munawaroh , Rima (Journal of Pharmaceutical and Sciences, 2026)
Crystal guava leaves (Psidium guajava L. Cultivar Kristal) are plants that have potential as antibacterial agents against bacteria that cause diarrhea because they belong to the Psidium guajava L. species, which is widely reported to contain bioactive compounds such as flavonoids, tannins, and alkaloids. This study was conducted to determine the antibacterial activity of crystal guava leaves and the group of compounds that act as antibacterial agents. The study design was experimental, using ethanol extracts and decoctions of crystal guava leaves made at concentrations of 40% w/v, 20% w/v, 10% w/v, and 5% w/v and tested on bacteria that cause diarrhea, namely Escherichia coli and Shigella sonnei, using the well diffusion method. Then, TLC-Bioautography was performed to detect the compound components. Statistical data analysis using SPSS began with normality, homogeneity, Kruskal-Wallis, and Mann-Whitney tests. The results showed that the 40% w/v concentration had the largest inhibition zone in both extracts. The compounds contained in the ethanol extract and crystal guava leaf decoction were flavonoids, alkaloids, and tannins. Meanwhile, the specific compound that acts as an antibacterial agent in ethanol extracts and crystal guava leaf decoction is the flavonoid group, specifically quercetin. The Kruskal-Wallis test with a p-value of 0,001 < 0,005 showed that there was a significant difference between concentrations. Further analysis using the Mann-Whitney test showed that the 40% concentration group was significantly different from the 5% concentration group.